2015
DOI: 10.4038/tar.v26i2.8097
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance assessment of major irrigation systems in Upper Deduru Oya Basin

Abstract: Performance assessment of irrigation systems plays a vital role to self-evaluate them so that interventions could be made to improve the functioning of the systems. This study was conducted to assess water delivery and supply performances and the agricultural productivity in three major irrigation systems, namely, Batalagoda, Hakwatuna Oya and Kimbulwana Oya in the upper Deduru Oya river basin and comparatively evaluate them based on the estimated values of selected performance indicators. Secondary data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Notwithstanding the rising trend, there is a lot of variation between the years, the lowest value being 0.85 and 0.94 kgm -3 as the highest value. The value of OPIS was found to range from 8.80-28.78 kgm -3 for rice in Sri Lanka (Lakmali et al, 2015). According to De Fraiture and Garces-Restrepo (1997), a closer analysis of irrigation and rainfall showed that if rainfall is higher than irrigation needed, the value of OPIS is high but less in the dry season.…”
Section: Output Per Unit Irrigation Supply (Opis)mentioning
confidence: 98%
“…Notwithstanding the rising trend, there is a lot of variation between the years, the lowest value being 0.85 and 0.94 kgm -3 as the highest value. The value of OPIS was found to range from 8.80-28.78 kgm -3 for rice in Sri Lanka (Lakmali et al, 2015). According to De Fraiture and Garces-Restrepo (1997), a closer analysis of irrigation and rainfall showed that if rainfall is higher than irrigation needed, the value of OPIS is high but less in the dry season.…”
Section: Output Per Unit Irrigation Supply (Opis)mentioning
confidence: 98%
“…Water as a critical input determines the crops yields and hence the livelihood of farmers in the Hakwatuna Oya irrigation scheme. It was found by other researchers that 78% of the farmers have no other income source except crop production in the Hakwatuna Oya irrigation scheme (Lakmali, 2015). Therefore, farmers are ready to fight and steal water as long as they have access to water.…”
Section: Water Conflicts In Hakwatuna Oya Irrigation Schemementioning
confidence: 99%
“…Irrigation water supply is considered the main factor from the point of view of irrigation system assessment. Hence, the irrigation system's water supply performance can be assessed, and field irrigation efficiency can be estimated [41]. An approach based on water balance was thus followed.…”
Section: Baseline Scenariomentioning
confidence: 99%